2019
DOI: 10.5858/arpa.2018-0002-oa
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Evaluation of Seegene Allplex Gastrointestinal, Luminex xTAG Gastrointestinal Pathogen Panel, and BD MAX Enteric Assays for Detection of Gastrointestinal Pathogens in Clinical Stool Specimens

Abstract: Context.— Infectious gastroenteritis is caused by various pathogens, including bacteria, viruses, and parasites. Objective.— To compare the performance of Seegene Allplex Gastrointestinal (24 targets: 13 bacteria, 5 viruses, and 6 parasites in 4 panels), Luminex xTAG Gastrointestinal Pathogen Panel (15 targets: 9 bacteria, 3 viruses, and 3 parasites), and BD MAX Enteric panel (5 bacteria and 3 parasites). We estimated the agr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
10
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(12 citation statements)
references
References 28 publications
1
10
1
Order By: Relevance
“…Among them, one included a unique stool positive for parasites (Cryptosporidium spp.) which was detected by the assay [13]. Another study, with a more consistent cohort, observed performances slightly lower to ours, with 92%, 100%, and 78% sensitivity for G. duodenalis, E. histolytica \, and Cryptosporidium spp., respectively [14].…”
Section: Discussioncontrasting
confidence: 72%
“…Among them, one included a unique stool positive for parasites (Cryptosporidium spp.) which was detected by the assay [13]. Another study, with a more consistent cohort, observed performances slightly lower to ours, with 92%, 100%, and 78% sensitivity for G. duodenalis, E. histolytica \, and Cryptosporidium spp., respectively [14].…”
Section: Discussioncontrasting
confidence: 72%
“…The multiplex LDT showed a very good sensitivity and specificity. The LDT was at least as sensitive in the detection of both viruses as a CE-cleared reference assay, which claims to have a limit of detection (LoD) of 75 tissue-culture infectious dose 50 (TCID 50 ) units per milliliter sample for norovirus G1, 5 TCID 50 /ml for norovirus G2, and 50 RNA copies per reaction for rotavirus according to the manufacturer (user manual Allplex™ GI-virus assay 05/2017 V2.0), and that has demonstrated excellent agreement with other molecular assays for stool pathogen diagnostics [17].…”
Section: Discussionmentioning
confidence: 99%
“…The BD MAX TM Enteric Bacterial Panel PCR clearly improves the diagnosis of Campylobacter sp. infections by enabling the laboratories to deliver fast and targeted results to their clinicians [6,7]. Syndromic approaches now replace the traditional research by culture.…”
Section: Discussionmentioning
confidence: 99%